2018
DOI: 10.1097/hco.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and fitness for the prevention of hypertension

Abstract: To lower the risk of hypertension, promoting physical activity and improving fitness, especially CRF, should be encouraged. More research is needed to determine the effects of sedentary behavior, resistance exercise, and muscle strength on the development of hypertension across diverse populations and settings. Future studies should focus on dose-response relationships of exercise and physical activity with the development of hypertension to determine the minimal and optimal amount of exercise and physical act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
68
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(86 citation statements)
references
References 63 publications
6
68
0
3
Order By: Relevance
“…While blood pressure can usually be best regulated through lifestyle modifications before it reaches the stage of hypertension, there is a range of treatment options 5 . Lifestyle adjustments, including physical activity and exercise, are the standard first-line treatments for hypertension 6 . It is well known that favorable physiological changes and overall health benefits are associated with regular physical activity 7 .…”
Section: Introductionmentioning
confidence: 99%
“…While blood pressure can usually be best regulated through lifestyle modifications before it reaches the stage of hypertension, there is a range of treatment options 5 . Lifestyle adjustments, including physical activity and exercise, are the standard first-line treatments for hypertension 6 . It is well known that favorable physiological changes and overall health benefits are associated with regular physical activity 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Those who did regular exercise had lower score of global sleep score. Bakker, Sui, Brellenthin, and Lee (2018) stated that exercise is included in the front line to treat patients with hypertension. During the data collection for this study, we found that majority of rural participants said regular exercise was not a common practice because they viewed it as a part of their daily physical activity during working such as walking or farming.…”
Section: Discussionmentioning
confidence: 99%
“…44 Nevertheless, if on one hand the major effect of exercise training is recorded in hypertensive conditions, on the other hand the training inhibits the progression from normal to pre-hypertension and from pre-hypertension to hypertension. 43,[45][46][47][48] Therefore, physical exercise represents a powerful therapeutic tool to prevent the development of hypertension, especially in high-risk populations like diabetic patients or individuals with family history of hypertension.…”
Section: E Xercis E Tr Aining a S Effec Tive Ther Apeuti C Tool In mentioning
confidence: 99%